Effects of dressing procedures upon yield and quality of the beef tenderloin - De Felicio, P.E.; Allen, Dell M.; Kastner, Curtis L. (Kansas State University. Agricultural Experiment Station, 2011)
Removing kidney fat at slaughter did not affect (P>.05) the chilled or chilled-and-aged weights of the tenderloin. But small differences in tenderness and color at the beginning of the display period favored the conventional dressing procedure.
Keywords: Beef; Beef tenderloin; Yield grade; Quality grade